2017
DOI: 10.21468/scipostphys.2.3.016
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Gravity and the Dark Universe

Abstract: To MariaRecent theoretical progress indicates that spacetime and gravity emerge together from the entanglement structure of an underlying microscopic theory. These ideas are best understood in Anti-de Sitter space, where they rely on the area law for entanglement entropy. The extension to de Sitter space requires taking into account the entropy and temperature associated with the cosmological horizon. Using insights from string theory, black hole physics and quantum information theory we argue that the positiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
604
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 456 publications
(620 citation statements)
references
References 102 publications
13
604
0
3
Order By: Relevance
“…As a future direction, we may consider the thermodynamic volume in an inflation model or de Sitter space. In these cases, the thermodynamic volume is related to the slow roll parameter of inflation models and it is interesting to see if the thermodynamic volume plays a role of an effective volume describing dark matter [16] .…”
Section: Physical Interpretation and Discussionmentioning
confidence: 99%
“…As a future direction, we may consider the thermodynamic volume in an inflation model or de Sitter space. In these cases, the thermodynamic volume is related to the slow roll parameter of inflation models and it is interesting to see if the thermodynamic volume plays a role of an effective volume describing dark matter [16] .…”
Section: Physical Interpretation and Discussionmentioning
confidence: 99%
“…Inspired by the emergent gravity models proposed by Verlinde in [1,2], we propose the induced gravity from higher dimensional spacetime which gives rise to the similar mechanism. We will modify the Einstein field equation in 3+1 dimensional spacetime at the cosmological scale,…”
Section: A Toy Model For the Late Universementioning
confidence: 98%
“…Although E. Verlinde suggested similar modifications of Newtonian dynamics as in MOND theories [2], which emerges with different underlining physical origin, there is no covariant equations of motion for the gravitational waves. While for our toy model in the previous sections, we have shown that the Einstein equations are not necessarily modified in our scenarios.…”
Section: Of Icgac-xiii and Ik-15 On Gravitation Astrophysics And Cosmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work on entropic gravity by Erik Verlinde [1,2] has initiated a recovery of earlier work by the author on the thermodynamics of diffuse interfaces [3] and stimulated a generalization of this approach. The approach depicted in the present article draws on a combination of the very forceful and fundamental concepts of entropy, of the phase-field method and of the Lagrange formalism.…”
Section: Introductionmentioning
confidence: 99%